Community service and initiation rites as means of educational acculturation in John B. Lacson Foundation Maritime University-Molo - Emague, Roland John Cyril F (University of the Philippines Visayas, 2014)
This research reported findings of an exploratory qualitative study examining the process of educational acculturation in John B. Lacson Foundation maritime University-Molo. It. described the ; 1.) nature of the community service and initiation rites as means of acculturation, 2.) the meanings and values derived from the various rituals and practices, as well as 3.) the comparison of the perceptions and learnings of new students and graduating marine students towards the practice. This study in a form of a narrative inquiry approach collected the data through key-informant interviews with the organizers of the school's annual practice and focus-group discussions (FGD) composed of new students and graduating marine students of JBLFMU-Molo. Using Krueger's Systematic Analysis Process, the results revealed that the school's community service and initiation rites are conducted in order to reflect the goals of the school, and serves as an avenue of inculcating the school culture to the students. The result also proved that the school's community service and initiation rites vividly act as a process of educational acculturation by which the school culture is successfully transmitted to the students by learning and imbibing it following the pattern and concept of the derived acculturation model.